Kebijakan Pemerintah Untuk Meningkatkan Akses Pendidikan Bagi Masyarakat Kurang Mampu - Fatmawati, Fifi; Fadillah, Nuzulul; Faizi, Ahmad; Kurnia, Heri (Innovations in Multidisciplinary Education Journal, 2025)
This study aims to analyze government policies in increasing access to education for the underprivileged. Quality education is an important factor in creating opportunity and social mobility. However, disadvantaged communities often face challenges in accessing education due to financial and infrastructure constraints. Therefore, the government has implemented various policies to overcome this problem. This research involves analyzing government policies, such as scholarship programs, educational subsidies, building schools in remote areas, and developing educational infrastructure. The results of the analysis show that government policies have succeeded in increasing access to education for underprivileged communities, although there are still challenges that need to be overcome. This research provides insight into the effectiveness of government policies in reducing disparities in access to education and provides recommendations for further improvement.